A new whitefly genus and species, Aleuroparvus theae Dubey (Hemiptera: Aleyrodidae) colonising Assam tea (Camellia sinensis) and Cinnamomum bejolghota, in North-East India - Dubey, Anil Kumar (Zootaxa, 2018)
Puparia of a new whitefly genus and species, Aleuroparvus theae Dubey gen. et sp. nov. are described along with drawings, habitus and type images of habitus and types, and scanning electron microscope microphotographs. It is found infesting an economically important plant, Assam tea, Camellia sinensis (L.) (Theaceae) in Assam, and Cinnamomum bejolghota (Hamilton) (Lauraceae) in Arunachal Pradesh, India. Puparia of A. theae are dimorphic, the females being larger than males. The puparia of the new genus differ from all other genera in having smaller ventral surface, submarginal wax secreting pores and dorsal submargin separated from the dorsal disc by a submarginal ridge. The diagnostic characteristics for puparia of the new genus are compared with closely related genera, Aleuroclava Singh, Aleuropleurocelus Drews & Sampson, Dialeuropora Quaintance & Baker, Tetralicia Harrison and Tetraleurodes Cockerell.